Church, War and Politics: The Cathedral Chapter of Puebla during the French Intervention (Mexico, 1861-1864) - Rosas, Sergio (2021)
This chapter aims to analyze the composition of the Cathedral Chapter of Puebla (Mexico), as well as its political position in the face of the French intervention in that country between 1861 and 1864. Based on the documentation of the chapter itself, the paper argues that, if Although the canons were open to negotiating with the civil authorities in power, whether liberal or foreign, they maintained two aspects as the inalienable basis of their public position: the defense of the central position of the Chapter as the authority of the episcopal city and the defense railway of ecclesiastical goods.